Memahami Manajemen Media Massa Untuk Publikasi Artikel bagi Penulis Pemula - Simanjuntak, Sahata (FDIK IAIN Padangsidimpuan, 2021)
Mass media have crucial roles in propogating information in society. News published through mass media, both the positive and the negative ones will be so highly accessible to public that they influence the way society thinks. If the published information is true and honest, it will result in positive impacts. On the other hand, if the published information is untrue, dishonest, and it instigates hatred, it will negative impacts and it can even trigger conflicts amongst society members. For those reasons, according to John Hohenberg, news in mass media must al all times prioritize the factors of actuality, honesty, and education. To carry out those functions, it is not an overstatement to say that mass mediaÂ are said to uphold noble duties playing big roles in educating the nation.